A Profile of Reproductive Health Awareness Character among Early Adolescents in Primary Education in Bandung City - Handayani, Dini Saraswati; Suryadi, Ace; Wahyudin, Dinn; Nurdin, Encep Syarif; Riyanti, Yanti; Megawati, Anita (Universitas Pendidikan Indonesia, 2025)
Reproductive health issues among adolescent girls are a global concern, particularly during early adolescence, a critical phase that significantly influences the quality of future generations. This study aimed to identify changes in growth, development, and knowledge related to reproductive health among girls aged 9–12 years, a period classified as early adolescence. The study employed a quantitative approach with a cross-sectional design. A total of 263 adolescent girls were selected using purposive sampling. The findings revealed that 52.47% of the participants were categorized as underweight, indicating nutritional problems that may have serious implications for reproductive health. Adolescent girls with poor nutritional status are at risk of reproductive function disorders, including irregular menstrual cycles and reduced reproductive health quality. In the long term, this condition may increase the likelihood of giving birth to babies with low birth weight (LBW), a significant factor contributing to stunting in the next generation. These findings highlight the urgent need for multidisciplinary interventions, including reproductive health education at the primary education level, to foster awareness and concern for reproductive health. Developing caring character and promoting reproductive health awareness among adolescent girls are vital as part of a long-term investment in sustainable national development.